químicos das folhas de Qualea grandiflora: atribuição dos dados de RMN de dois flavonóides glicosilados acilados diastereoisoméricos - Ayres, Mariane Cruz Costa; Escórcio, Samuel Portela; Costa, Danielly Albuquerque da; Chaves, Mariana H.; Vieira Júnior, Gerardo Magela [UNESP]; Cavalheiro, Alberto José [UNESP] (Sociedade Brasileira de Química, 2008)
Phytochemical investigation from leaves of the Qualea grandiflora (Vochysiaceae) resulted in the isolation and identification of kaempferol-3-O-α-L-(4-E-p-coumaroyl)-rhamnoside, kaempferol-3-O-α-L-(4-Z-p-coumaroyl)-rhamnoside, squalene, phytol, lupeol, α-amyrin, β-amyrin, sitosterol, sitostenone, sitosterol-3-O-β-D-glucopyranoside, ursolic and oleanolic acids. The structures of the compounds were identified by 1D- and 2D-NMR experiments, mass and UV spectrometry and comparison with literature data.
Chemical constituents from leaves of the Qualea grandiflora: attribution of the NMR data of two diastereoisomeric acylated flavonoid glycosids
Keywords: Qualea grandiflora; Vochysiaceae; acylated kaempferol glycosids